To solve the expression \(-4 (3 + 12^0) + 15^0\) using the zero power rule, we need to recognize that any non-zero number raised to the power of zero equals 1. Therefore, we have:
- \(12^0 = 1\)
- \(15^0 = 1\)
Now, we can substitute these values into the expression:
\[ -4 (3 + 12^0) + 15^0 = -4 (3 + 1) + 1 \]
Next, we perform the addition inside the parentheses:
\[ = -4 (4) + 1 \]
Now, we multiply:
\[ = -16 + 1 \]
Finally, we add:
\[ = -15 \]
Now, let's check which of the options corresponds to our calculations:
A. \(-4 (3+ 12^0) + 15^0 = -4 (3+1) + 1 = -4 \times 4 + 1 = -16 + 1 = -15\) (Correct)
B. \(-4 (3 + 12^0) + 15^0 = -4 (15) + 15 = -60 + 15 = -45\) (Incorrect)
C. \(-4 (3 + 12^0) + 15^0 = -4 (15) + 1 = -60 + 1 = -59\) (Incorrect)
D. \(-4 (3 + 12^0) + 15^0 = -4 (3 + 1) + 1 = -4 \times 4 + 1 = -16 + 1 = -15\) (This is rephrased, but still correct).
So, the correct answer is A.